Transformasi Evaluasi Pendidikan Islam dari Penilaian Kognitif ke Pembentukan Karakter Peserta Didik - Fikri, Muhammad; Firdayeni, Firdayeni; JamilusJamilus, Jamilus (YASIN, 2025)
Although evaluation in Islamic education has been widely studied, particularly in relation to the assessment of cognitive learning outcomes, research that specifically highlights the transformation of evaluation from a dominance of cognitive assessment toward the formation of student character remains relatively limited and tends to be normative–conceptual, thereby failing to provide a comprehensive empirical picture of character evaluation practices in educational institutions. This study aimed to analyze forms of transformation in Islamic education evaluation, identify character evaluation practices implemented by teachers, and reveal the implementation challenges involved in integrating cognitive, affective, and psychomotor assessment in a holistic manner. The study employed a qualitative approach with a case study design, involving Islamic Religious Education teachers at the secondary education level selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and a review of evaluation documents, and were then analyzed using systematic, multilayered thematic analysis. The findings show that evaluation in Islamic education continues to be dominated by cognitive assessment based on written tests, while character assessment is largely conducted implicitly through observation of attitudes and habituation, without the support of standardized authentic instruments. These findings contribute to the development of Islamic education evaluation theory grounded in the integration of tarbiyah, ta‘lim, and ta’dib, and broaden understanding of the importance of evaluation as an instrument for shaping adab and student character. The study concludes by underscoring the urgency of strengthening authentic and reflective evaluation in Islamic education and recommends the development of systematic character evaluation instruments for educators and policymakers so that assessment systems become more holistic, sustainable, and oriented toward student character formation.